Difficulties LGBTQ Face in American High Schools - Zhou, Nan (Transactions on Social Science, Education and Humanities Research, 2024)
LGBTQ students in American high schools encounter a number of challenges that can significantly impact their sense of belonging, mental health, and academic ability. Despite progress in the field of LGBTQ rights, many children continue to face discriminatory regulations and homophobic and transphobic statements in the classroom. This research tries to examine the complexities of the issues that LGBTQ youth face, emphasizing the importance of targeted interventions to promote inclusive learning environments. This study intends to shed light on the factors that influence both unfriendly and supportive school settings for LGBTQ children by looking into typical negative attitudes and actions in schools, as well as protective methods and advocacy efforts. The analysis will focus on the efficacy of current initiatives for reducing prejudice and increasing school inclusion, adding to broader discussions about LGBTQ rights, education reform, and social justice. This study emphasizes the urgent need for comprehensive methods to protecting LGBTQ students and creating conditions in which all students can thrive. This study seeks to inform targeted interventions and legislative reforms that promote fairness, acceptance, and safety for LGBTQ children in American high schools by investigating the complicated dynamics that exist within educational environments.